Epidemiological, diagnostic, therapeutic and prognostic impact of hepatitis B and D virus infection on hepatocellular carcinoma: A review of the literature - Bruni, Angelo; Castellana, Chiara; Dajti, Elton; Barbara, Giovanni; Marasco, Giovanni; Maida, Marcello; Serviddio, Gaetano; Facciorusso, Antonio (Virology (New York, N.Y.), 2024)
Hepatocellular carcinoma (HCC) accounts for >90% of primary liver cancer cases, and chronic infections with hepatitis B virus (HBV) and hepatitis D virus (HDV) are major contributors. A comprehensive literature review was conducted using the MEDLINE (PubMed) database, focusing on studies related to HBV, HDV, and HCC. HBV contributes to HCC through mechanisms like viral integration into the host genome, chronic inflammation, and immune modulation, leading to genomic instability and altered cell signaling. HDV exacerbates HBV-induced liver damage, accelerating fibrosis and cirrhosis, and significantly increasing HCC risk. Antiviral therapies and vaccinations have majorly reduced the burden of HBV-related HCC, but HDV remains challenging to treat due to limited therapeutic options. Emerging treatments like Bulevirtide showed promising results. This review highlights the critical impact of HBV and HDV co-infections on HCC development, emphasizing the need for more effective therapeutic strategies. While advances in antiviral therapies have reduced the incidence of HBV-related HCC, the high burden of HDV-related complications persists. Future research should focus on improving treatments for HDV and understanding its unique contribution to HCC pathogenesis.